A non-invasive method to investigate foot bone kinematics - Rauner, K.; Krautter, A.; Lehner, S.; Mitternacht, J.; Senner, V. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate whether image correlation photometry in combination with an inverse dynamics foot model is capable of investigating foot bone kinematics. Thus an explorative test setup with one participant was used to acquire the motion data with ARAMISTM (GOM, Braunschweig, Germany). The motion data enabled a customized inverse dynamics foot model to reproduce the recorded motion and simulate intrinsic movement. Navicular drop was 10.5mm and maximal motion angle did not exceed 23°. The calculated results of navicular drop, range of motion and course of angle over time are promising in comparison to studies using bone pins.